Genomics and structure/function studies of Rhabdoviridae proteins involved in replication and transcription - Assenberg, R; Delmas, O; Morin, B; Graham, S; De Lamballerie, X; Laubert, C; Coutard, B; Grimes, J; Neyts, J; Owens, R; Brandt, B; Gorbalenya, A; et al. (2010)
Some mammalian rhabdoviruses may infect humans, and also infect invertebrates, dogs, and bats, which may act as vectors transmitting viruses among different host species. The VIZIER programme, an EU-funded FP6 program, has characterized viruses that belong to the Vesiculovirus, Ephemerovirus and Lyssavirus genera of the Rhabdoviridae family to perform ground-breaking research on the identification of potential new drug targets against these RNA viruses through comprehensive structural characterization of the replicative machinery. The contribution of VIZIER programme was of several orders. First, it contributed substantially to research aimed at understanding the origin, evolution and diversity of rhabdoviruses. This diversity was then used to obtain further structural information on the proteins involved in replication. Two strategies were used to produce recombinant proteins by expression of both full length or domain constructs in either E. coli or insect cells, using the baculovirus system. In both cases, parallel cloning and expression screening at small-scale of multiple constructs based on different viruses including the addition of fusion tags, was key to the rapid generation of expression data. As a result, some progress has been made in the VIZIER programme towards dissecting the multi-functional L protein into components suitable for structural and functional studies. However, the phosphoprotein polymerase co-factor and the structural matrix protein, which play a number of roles during viral replication and drives viral assembly, have both proved much more amenable to structural biology. Applying the multi-construct/multi-virus approach central to protein production processes in VIZIER has yielded new structural information which may ultimately be exploitable in the derivation of novel ways of intervening in viral replication. © 2010 Elsevier B.V.